The Volatility Spillover Effect among A-Share and H- Share Markets in China: Under the Influence of Shanghai-Hong Kong Stock Connect - You, Li (2019)
Researches on the dynamic correlation of volatility between markets are essential to prevent risk and the spread of financial crises. So far, the literature mainly focused on exploring volatility spillovers between developed countries and less literature on developing countries. On the other hand, the open-up capital market policy greatly affected the correlation between equity markets in mainland China and Hong Kong. Considering the influence of Shanghai-Hong Kong Stock Connect and recognising the variety in the volatility spillovers between A and H shares is conducive to understanding the risk transfer between two stock markets, which provides the theoretical foundation for risk control. By using the daily data, this paper shed light on the volatility spillover effects between the two main stock markets in China and directional volatility spillovers of the various industries in these two markets through VAR-BEKK-GARCH and Diebold Yilmaz method. According to the empirical results, the opening of Shanghai-Hong Kong Stock Connect makes a considerable difference to the volatility spillover effect between two capital markets. Before the practice of the program, the volatility spillover effects were unidirectional from Hong Kong to mainland China. However, empirical findings demonstrate the dominance of A-share market, as the main driver among these two markets after the implementation of the open-up policy and further, the introduction of the stock connect program greatly enhanced the volatility spillover effect from the mainland China market to the H-share market. The spillovers between these two capital markets turns from unidirectional to bidirectional. Furthermore, from the perspective of industry, it is found that with the announcement of the stock connect program, the main sectors that make significant contributions to the volatility spillover effect, change from the secondary industry to the tertiary industry. These findings provide a reference for investors to make informed decisions while choosing strategies of risk diversification and hedging.